(untitled) (Scientific journal of the Fergana State University, 2026)
This paper analyzes the fertility indicators of irrigated light gray soils and presents new, improved agricultural technologies for growing Saperavi, Khindogni, and Bayan Shirey grape varieties on these soils. The yield dynamics of these grape varieties are analyzed, and strategies for achieving high grape yields are outlined.